Reimagining the Potential of Feminist Epistemologies in Science - Piper Sledge; Collin Rice (Feminist Philosophy Quarterly)
Standpoint and feminist epistemologies have provided a number of theoretical advancements concerning the ways we ought to think about the production of knowledge across scientific disciplines. Despite these theoretical contributions, in this paper, we critique what we call the “thin” application/implementation of diversity within the epistemic practices of science and academia. As an alternative, we place these theories in conversation with recent philosophy of science and Indigenous epistemology focused on the epistemic aims of communal explanation and understanding. We contend that conceptions of diversity that focus on the standpoints of individual researchers and attempts to merely “add diversity and stir” make it more difficult for these epistemic goals of science to be achieved. We then argue that for diversity to contribute to increasing the variety of explanations and promote more substantive understanding of epistemic communities requires a “thick” implementation that incorporates lessons from standpoint, feminist, and Indigenous epistemologies into the heart of scientific practices.